Metallurgical studies with the HIPPO diffractometer at LANSCE. (January 2015) - Reiche, H. M.; Carpenter, J. S.; Stein, F.; Tomida, T.; Vogel, S. C.
<x content-type="archive" xml:space="preserve">Abstract</x> Advantages of neutron diffraction for metallurgical studies are highlighted with research examples performed on the High Pressure - Preferred Orientation diffractometer at the Los Alamos Neutron Science Center. The previously inconclusive crystallographic structure of the Fe–Al ϵ-phase, stable between 1095 and 1231°C, was determined by in situ neutron diffraction to have the formula Fe5Al8 with a body centred cubic structure of the Hume–Rothery Cu5Zn8 type at 1120°C. As a second example, the effect of variations in accumulative roll bonding processing parameters on interfacial structure, hardness, and thermal stability are explored for lamellar Cu–Nb multilayers with individual layer thicknesses of 20 nm. Furthermore, we derive an explanation for observed texture memory effects during the α→γ→α transformation cycle in a 0·1%C–1%Mn hot rolled steel sheet from the double Kurdjumov–Sachs relationship. Finally, we present in situ results of a Zr–2·5Nb sample heated into the β-field and subsequently compressed by 20% via our recently developed creep furnace which uniquely allows deconvolution of the effects of heating, phase transformations, deformation and cooling on the texture evolution. On souligne les avantages de la diffraction des neutrons pour les études métallurgiques, avec des exemples de la recherche effectuée avec le diffractomètre à haute pression – à orientation préférée au Centre de la Science des Neutrons de Los Alamos. On a déterminé par diffraction in situ des neutrons, que la structure cristallographique auparavant peu concluante de la phase ϵ de Fe–Al, stable entre 1095 et 1231°C, avait la formule Fe5Al8 avec une structure cubique centrée du type Cu5Zn8 de Hume-Rothery, à 1120°C. Comme second exemple, on explore l'effet des variations des paramètres de traitement de colaminage cumulatif sur la structure de l'interface, sur la dureté et sur la stabilité thermique de multicouches lamellaires de Cu–Nb, avec épaisseur de 20 nm des couches individuelles. De plus, on dérive une explication des effets observés de la mémoire de texture lors du cycle de transformation α→γ→α dans une tôle d'acier roulée à chaud de 0·1%C–1%Mn, à partir de la relation de Kurdjumov–Sachs. Finalement, nous présentons les résultats in situ d'un échantillon de Zr-2·5Nb chauffé dans la plage β et subséquemment comprimé de 20% au moyen de notre four de fluage développé récemment, qui permet de déconvolutionner de façon unique les effets du chauffage, des transformations de phase, de la déformation et du refroidissement sur l'évolution de la texture.